Phenolic profile and antioxidant properties of sand rice (Agriophyllum squarrosum) as affected by cooking and in vitro digestion. (26th March 2019) - Wang, Qi; Shao, Hongjun; Zhang, Zhong; Yan, Shuaishuai; Huang, Feng; Zhang, Hong; Yang, Xinbing
Abstract: BACKGROUND: Sand rice ( Agriophyllum squarrosum ) is an underutilized pseudocereal bearing edible seeds. In this study, the phenolics and antioxidant activity of sand rice seeds after cooking and in vitro digestion were extensively investigated. RESULTS: Total phenolic content (TPC) of the sand rice seeds was slightly increased whereas total flavonoid content (TFC) decreased after boiling. Furthermore, nine compounds were detected in the uncooked seeds, with hyperoside (169.19 ± 6.59 µg g −1 dry weight (DW)), protocatechuic acid (167.46 ± 7.21 µg g −1 DW), and rutin (83.15 ± 3.26 µg g −1 DW) as the major components. Apart from the bioaccessible phenolics in the aqueous fraction, these compounds retained in the solid residue of the porridge were released to varying degrees during simulated digestion. In addition, these phenolic extracts also exerted considerable antioxidant potency, which was positively correlated with their corresponding TPC, TFC, and phenolic profiles. CONCLUSION: These results indicated that both boiling and in vitro digestive treatments could considerably enhance the release of bioactive compounds and thus contribute antioxidant properties to sand rice porridge. These findings suggest that sand rice seed is a potential functional food and an excellent natural antioxidant source. © 2019 Society of Chemical Industry